Vesico-Ureteral Reflux and Reflux Nephropathy in Children with Recurrent Urinary Tract Infection - Taralan Tambunan (Paediatrica Indonesiana, 1996)
We reviewed clinical and laboratory findings of patients with recurrent urinary Uact infections (UTI) to detect the presence of vesico-ureteral reflux (VUR) or reflux nephropathy (RN). Only patients with evidence of more than 2 bouts of UTI's treated at the Department of Child Health, Cipto Mangunkusumo Hospital during the period from October 1, 1992 to September 30, 1993 were studied. There were 30 paÂtients (15 boys, 15 girls) ranging in age from 2 months to 16 years (mean age = 5.5 years). RN as detected on dimercaptosuccinic acid (DMSA) scanning was found in 21 patients (12 unilateral, 9 bilateral). Mictiocyctourography (MCU) was done in 22 patients, revealing VUR in 14 patients, 10 of them showed renal scarring on DMSA scanning. Most of die patients has the duration of illness of less than 2 years. Clinical symptoms and signs (hypertension, proteinuria, increased plasma urea / creatinine) alone or in combination were more commonly found in patients with RN than in those without RN. The high prevalence of VUR and RN in patients with recurrent UTI in our senes (63% and 70%, respectively), should draw our attention to detect UTI in its earliest stage, to be able to treat the patient promptly in order to prevent RN which eventually progresses into renal failure.